VIVAT, CVAT and All That : New Forms of Value-Added Tax for Federal Systems - Keen, Michael (Washington, D.C. : International Monetary Fund, 2000)
Conventional wisdom has it that the value-added tax is not a suitable instrument for lower-level jurisdictions ('provinces') in a federal system. The problems that arise when it is so used have become a serious constraint on the development of the VAT-and closer economic integration-in Brazil, the EU, India and elsewhere. This paper describes and compares two recent proposals for forms of VAT intended to alleviate these difficulties: the VIVAT and the CVAT. Both enable the VAT chain to be preserved on inter-provincial trade without compromising the destination principle (allowing provinces to tax consumption at different rates) or introducing new scope for game-playing by the provinces. The key difference between them is that the CVAT requires sellers to discriminate between buyers located in different provinces of the federation, whereas VIVAT requires them to discriminate between registered and non-registered buyers. Where the balance of advantage between the two lies is not entirely obvious.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet